ANALISIS DESKRIPTIF TINGKAT PERILAKU PROKRASTINASI AKADEMIK SISWA KELAS X MIPA - Rusdana, Nita Laila; Fitriana, Siti; Mujiono, Mujiono (Universitas PGRI Semarang, 2022)
Abstract. Academic procrastination behavior is the behavior of procrastinating to do academic tasks that is done intentionally and repeatedly. Academic procrastination behavior can also adversely affect student achievement. This study aims to determine the level of academic procrastination behavior of class X Mipa students at SMAN 1 Bae Kudus. This type of research is quantitative research with a descriptive approach. The population in this study consisted of 250 students and the samples taken were 214 students. Data analysis in this study was obtained through a student academic procrastination questionnaire consisting of 35 closed statement items with 4 alternative answers. The results obtained in this study indicate that the level of academic procrastination behavior of class X Mipa students at SMAN 1 Bae Kudus is